Letter - Jones, J. W.
011-0142-001 TRADE UNION DELEGATION TO SPAIN. [BRANCH NO. 1/] [TRANSPORT & GENERAL WORKERS' UNION.] Branch Secretary's Address: 3 Hale End Rd. E.17. Phone; LARkswood 1576. Date : 11th February. 1937. Your Ref; WMC/KMS/269. Sir Walter Citrine. K.B.E General Secretary, T.U.C.G.C. Dear Sir, I have to acknowledge yours of the 10th, inst for which I thank you. My committee will consider at their next meeting the points made in your letter, whereupon I shall write further. Yours fraternally, J.W. Jones Secretary to Delegation. 292/946/11/142